HOW SOCIODRAMA-BASED HEROISM LEARNING SHAPES PRIMARY SCHOOL STUDENTS' NATIONAL CHARACTER: A QUALITATIVE STUDY - Aldy Ferdiyansyah; Fathul Jannah; Noorhapizah Noorhapizah; Akhmad Riandy Agusta; Rusmadi Rusmadi; Radina Radina (JURNAL EDUSCIENCE, 2026)
Purpose –This study aims to describe how sociodrama-based heroism learning shapes the character of friendship in elementary school students through contextual, participatory, and local history-based learning experiences.Methodology – This study uses a qualitative, phenomenological design. The research subjects included students in grades IV, V, and VI of SDN Sungai Miai 5 Banjarmasin, who served as actors and spectators in the sociodrama, and the class teacher, who served as a supporting informant. Subjects were selected purposively based on students' involvement in learning activities. Data collection was carried out through in-depth interviews, participatory observation, and learning documentation. Data analysis was carried out thematically through the stages of data reduction, data presentation, and meaning drawing.Findings – The study's results indicate that sociodrama learning shapes students' national character, as reflected in historical awareness, exemplary heroic figures, patriotism, social awareness, responsibility, and nationalistic attitudes. Students' emotional involvement in acting out local historical events encourages the interpretation of heroic values as experiences directly lived and reflected on, not merely understood cognitively.Contribution – This study makes conceptual and practical contributions by confirming that local history-based sociodrama is a relevant learning strategy for strengthening elementary school students' national character through meaningful, contextual learning experiences. These findings broaden understanding of national character education practices and can serve as a reference for teachers in designing more meaningful, contextual, and sustainable history learning in elementary schools.